Social Protection for Indonesian Migrant Workers: Between Urgency and the Complexity of Challenges - Sukamdi, Sukamdi; Zainudin, Zainudin; Supriadi, Arif Dahyan; Saragih, Tarimantan S.; Pitoyo, Agus Joko; Purwatiningsih, Sri; Ihwanudin, Idris; Pramasanti, An Nisa; Mahaganti, Fergie S.; Pradana, Fadly Eka; Hutabarat, Rendra H.; Siregar, Denny; Putra, Mochamad Andika (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2025)
Social protection for Indonesian Migrant Workers (IMWs) is a critical topic concerning the rights and welfare of migrant workers. This page covers different areas of social protection for IMW, including pre-departure planning, work in the target country, and reintegration upon return to the motherland. According to Law No. 18/2017, social protection is divided into three major stages that coincide with Maslow's hierarchy of needs theory. Although bilateral agreements with nations such as Hong Kong and Japan have had a favorable impact, issues in socialization, cross-country coordination, and monitoring in destination countries remain considerable. This study found that many IMWs are still uninformed of their rights, notably with Social Security Agency for Employment, due to a lack of information and access to adequate services. The novelty of this study lies in its integration of Maslow’s hierarchy with a policy-oriented framework for migrant worker protection, offering a fresh analytical lens to assess unmet needs at each migration stage. Recommendations include enhancing socialization, strengthening bilateral and international cooperation, digitizing services, enforcing stricter oversight, and improving reintegration and economic empowerment programs. These measures are expected to strengthen social protection for IMWs and ensure their welfare abroad.